The Wnt Signaling Pathway Effector TCF7L2 Mediates Olanzapine-Induced Weight Gain and Insulin Resistance - Li, Ranran; Ou, Jianjun; Li, Li; Yang, Ye; Zhao, Jingping; Wu, Renrong (Frontiers in Pharmacology, 2018)
Olanzapine is a widely used atypical antipsychotic medication for treatment of schizophrenia and is often associated with serious metabolic abnormalities including weight gain and impaired glucose tolerance. These metabolic side effects are severe clinical problems but the underpinning mechanism remains poorly understood. Recently, growing evidence suggests that Wnt signaling pathway has a critical role in the pathogenesis of schizophrenia and molecular cascades of antipsychotics action, of which Wnt signaling pathway key effector TCF7L2 is strongly associated with glucose homeostasis. In this study, we aim to explore the characteristics of metabolic disturbance induced by olanzapine and to elucidate the role of TCF7L2 in this process. C57BL/6 mice were subject to olanzapine (4 mg/kg/day), or olanzapine plus metformin (150 mg/kg/day), or saline respectively for 8 weeks. Metabolic indices and TCF7L2 expression levels in liver, skeletal muscle, adipose and pancreatic tissues were closely monitored. Olanzapine challenge induced remarkably increased body weight, fasting insulin, homeostasis model assessment-insulin resistance index and TCF7L2 protein expression in liver, skeletal muscle, and adipose tissues. Notably, these effects could be effectively ameliorated by metformin. In addition, we found that olanzapine-induced body weight gain and insulin resistance actively influence the expression of TCF7L2 in liver and skeletal muscle, and elevated level of insulin determines the increased expression of TCF7L2 in adipose tissue. Our results demonstrate that TCF7L2 participates in olanzapine-induced metabolic disturbance, which presents a novel mechanism for olanzapine-induced metabolic disturbance and a potential therapeutic target to prevent the associated metabolic side effects.